Enhancing extraction processes in the food industry - Lebovka, N. I. (Nikolai Ivanovich); Vorobiev, Eugene; Chemat, Farid (Boca Raton, FL. : CRC Press, 2012)
'Providing a clear description of different extraction methods, tools, and techniques, this book reviews modern approaches that enhance each extraction process. The text presents both classical and emerging extraction processes applied in food manufacture as well as the fundamentals of extraction and mechanical destruction techniques applied to plant materials and biosuspensions. The author discusses new results and methods related to bio- and supercritical fluid assisted extraction, extraction assisted by power ultrasonic, microwaves, induction heating, pulsed electric fields, arc discharge, ohmic heating, extrusion and vacuum, and various combined methods'--
Includes bibliographical references and index.
Keywords: Extraction (Chemistry).; Plant Extracts; Food industry and trade